Efficacy of Anthem, Anthem ATZ, Solstice, Keystone NXT, Corvus, and Surestart II in Glyphosate-Resistant Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
The best treatments provided excellent green foxtail, crabgrass, or shattercane control. All treatments dramatically increased corn yield compared to the control.
Keywords: Anthem; weed science; weed control; irrigated corn; glyphosate-resistant corn; tank mixes; herbicide